Negotiating Internet governance - Radu, Roxana (Oxford, United Kingdom New York, NY Oxford University Press, 2019)
This book provides an incisive analysis of the emergence and evolution of global Internet governance, revealing its mechanisms, key actors and dominant community practices. Based on extensive empirical analysis covering more than four decades, it presents the evolution of Internet regulation from the early days of networking to more recent debates on algorithms and artificial intelligence, putting into perspective its politically-mediated system of rules built on technical features and power differentials. For anyone interested in understanding contemporary global developments, this book is a primer on how norms of behaviour online and Internet regulation are renegotiated in numerous fora by a variety of actors - including governments, businesses, international organisations, civil society, technical and academic experts - and what that means for everyday users.
Introduction -- Deconstructing internet governance : a framework for analysis -- Revisiting the origins : the internet and its early governance -- Privatization and globalization of the internet -- The WSIS decade and the public-private partnership thirst -- Enacting internet governance : power and communities over time -- Conclusion : reflections on a global issue domain
Includes bibliographical references (pages 205-223) and index.
Keywords: Internet governance -- Law and legislation; Internet -- Law and legislation